Comparison of photopolymerization temperature increases in internal and external positions of composite and tooth cavities in real time: Incremental fillings of microhybrid composite vs. bulk filling of bulk fill composite. Issue 9 (September 2015) - Kim, Ryan Jin-Young; Son, Sung-Ae; Hwang, Ji-Yun; Lee, In-Bog; Seo, Deog-Gyu
Abstract Objectives This study evaluated temperature increases in the composite and pulpal side of dentin from incremental and bulk fillings in composite restorations. Methods Class-1 cavities (5 mm × 4 mm × 3 mm) were prepared in ten extracted third molars, filled with composite, and restored with two separate horizontal layers of Filtek Z250 (3M ESPE) in the incremental group or a single layer of SureFil SDR Flow (Dentsply) in the bulk-fill group (n = 5). After placing the specimens in a 36.5 °C water bath, temperatures were measured with eight thermocouples at the bottom center (BC), middle center (MC), top center (TC), bottom corner (BE), middle corner (ME), and top corner (TE) of the cavity, at the pulpal side of the dentin within the pulp chamber (PD), and in the curing light (CL) tip during light curing at 750 mW/cm2 for 20 s and then analyzed with one-way analysis of variance and Tukey's HSD tests (α = 0.01). Results Maximum temperatures ranged from 39.0 °C (PD 1st increment) to 60.0 °C (MC 1st increment) in the incremental group and from 42.0 °C (PD) to 74.9 °C (TC) in the bulk-fill group. In the incremental group, temperatures were similar between the 1st and 2nd increments, except at MC and BC. Conclusions Bulk-fill group exhibited a greater increase in temperature during composite restoration. Regardless of the filling technique, more heat was generated at the center than at the corner and at the top than at the bottom of the composite. PD temperatures increased by 3.1 °C and 5.5 °C in the incremental group and bulk-fill group, respectively. Clinical significance Although bulk fillings save clinical chair time, clinicians should be aware of the greater heat that is generated with increasing amounts of composites during polymerization, which can jeopardize the pulpal health, especially when a large and deep cavity is being restored.